Delivery of imiquimod to intestinal lymph nodes following oral administration - Chen, Haojie (2025)
The lymphatic system is highly involved in the progression of colorectal cancer (CRC), providing the pathway for metastasis and the environment for the immune response to cancer. Mesenteric lymph nodes (MLNs) and iliac lymph nodes (ILNs) drain the lymph from the colorectal region and are enriched in antigen-presenting cells, such as dendritic cells (DCs), as well as different types of lymphocytes. In these lymph nodes, activated DCs can stimulate naïve T cells to differentiate to CD8+ cytotoxic T cells and CD4+ T helper cells by cross-presenting tumour-associated antigens to them, resulting in the anti-tumour immune response. However, in CRC patients, activated DCs are downregulated by tumour cells in the tumour-draining LNs, frequently leading to poor therapeutic outcomes for patients receiving anti-tumour immunotherapy. Imiquimod (IMQ) is a powerful immune system activator, which can promote DCs activation via binding to toll-like receptor 7 on the DCs. However, the non-specific and extensive distribution of IMQ in the body may result in poor therapeutic outcomes in cancer patients and could lead to adverse effects. MLNs and ILNs are enriched in immature DCs and other lymphocytes and, therefore, are preferred tissues for immunomodulators. The delivery of IMQ into these lymph nodes in a targeted manner can promote the activation of DCs and improve the cross-presentation of tumour-associated antigens to naïve T cells. As a result, the tumour-mediated suppression of the immune system could be overcome, potentially leading to an improved therapeutic outcome in patients with CRC. In this PhD project, the chemically unmodified IMQ was initially assessed for its potential for lymphatic transport following oral administration. Due to its low lipophilicity and poor solubility in triglycerides, IMQ was not expected to be absorbed into the intestinal lymphatics. Therefore, the aim of this PhD project was to design highly lipophilic prodrugs of IMQ that can be transported into MLNs and ILNs, and efficiently release IMQ within these lymph nodes. This drug delivery approach takes advantage of the digestion of fat in the intestine. During the natural process of ingestion of dietary lipids, large lipoproteins, chylomicrons (CMs), are formed in the enterocytes. Due to the large size of CMs, they are absorbed into the lymph lacteals rather than blood capillaries. Thus, a drug molecule that has a high affinity to CMs has potential to be transported into the intestinal lymphatics via the CMs pathway. First, we developed bioanalytical methods for the determination of the concentration of IMQ in the biological samples. The bioanalytical method using liquid chromatography equipped with ultraviolet detector (HPLC-UV) had a lower limit of quantification (LLOQ) at 15 ng/mL, which allows the determination of IMQ in in vitro and ex vivo biological samples. In addition, the bioanalytical method using liquid chromatography with tandem mass spectrometry (LC-MS/MS) was developed and validated. The calibration curve showed good linearity from 1.25 to 4,000 ng/mL, which could be used for the determination of the concentration of IMQ in in vivo samples. Moreover, the LC-MS/MS bioanalytical method only required a small volume of plasma sample at 100 μL, which is important for work with small laboratory animals such as rats. Using the bioanalytical methods developed in this project, the pharmacokinetic (PK) and biodistribution (BD) profiles of IMQ in rats following oral administration were assessed. The oral bioavailability (Foral) of IMQ was limited (< 10%) with or without the presence of lipids. The plasma concentration-time profile of IMQ was prolonged and erratic following oral administration of unmodified IMQ at the dose of 8 mg/kg. In this project, we first reported the biodistribution of IMQ in the MLNs, ILNs, and other lymph nodes, which are the essential targeting areas for immune system activation. Interestingly, although IMQ is not a highly lipophilic molecule, it was widely distributed into tissues, including lymph nodes. The average concentrations of IMQ in MLNs and ILNs were 85.7 ± 103.2 ng/g and 99.8 ± 132.2 ng/g, respectively, at 1.5 h following oral administration of the drug, which was higher than its concentration in plasma (21.7 ± 20.4 ng/mL). Next, amide prodrugs of IMQ were designed and synthesised by conjugating IMQ with saturated and unsaturated medium- to long carbon chains fatty acids. The amidation of IMQ was achieved with N, N, N′, N′-tetramethylchloroformamidinium hexafluorophosphate and N-methylimidazole in N-methyl-2-pyrrolidone. This reaction provided a relatively high yield for the production of the prodrugs (70 – 90 %). The synthesised amide prodrugs were assessed for their lymphatic transport potential, determined by their in silico and in vitro affinities to CMs, as well as solubility in triglycerides. The assessments for the intestinal lymphatic transport of prodrugs showed that the developed lipophilic alkyl amide prodrugs have a substantial affinity to CMs. A promising prodrug candidate in this work is expected to resist the enzymatic hydrolysis in the intestine, but rapidly release the active moiety in the lymphatics. The biotransformation of prodrugs in relevant enzymatic environments representing intestinal lumen (simulated intestinal fluids with added esterase activity) and lymph (using plasma as lymph surrogate) was assessed. Additionally, in our work, brush border enzyme vesicles that were collected from rats’ small intestine were used to estimate the hydrolysis of prodrugs in the gastrointestinal tract. In vitro and ex vivo results suggested that all synthesised prodrugs were stable in the intestine (except prodrug 1, which was synthesised by conjugating IMQ with decanoic acid) and could efficiently release IMQ in the lymph fluid. Moreover, it was found that the unsaturation of fatty acid could facilitate IMQ release from the prodrugs in rat plasma. Subsequently, the most promising prodrug candidates (prodrug 5 and prodrug 8) were administered to rats to assess their pharmacokinetics and lymph nodes delivery. When prodrug 5 (synthesized by conjugating IMQ with myristoleic acid) and prodrug 8 (synthesized by conjugating IMQ with linoleic acid) were orally administered, the Foral of IMQ was not increased, but the plasma concentration-time profile of IMQ was not prolonged and erratic in comparison to oral administration of IMQ itself. This result suggests that the lipophilic prodrug approach did not significantly increase the systemic exposure to IMQ but potentially changed the absorption pathway of the drug. Therefore, the BD studies of IMQ following oral administration of prodrugs 5 and 8 were conducted to evaluate the intestinal lymphatic delivery. In vivo studies showed that the average concentrations of prodrugs 5 and 8 in the mesenteric lymph were 50- and 11-fold higher than their concentration in the plasma, respectively, suggesting that a substantial amount of prodrugs were transported into intestinal lymphatics. Moreover, the lymph-to-plasma ratio of the concentration of IMQ (released from the prodrug) was 1.9-fold and 1.7-fold following oral administration of prodrug 5 and prodrug 8, respectively, indicating that the prodrugs efficiently released IMQ in the mesenteric lymph. Importantly, the average concentration of IMQ in MLNs and ILNs was 11-fold and 9-fold higher, respectively, than it was in plasma at 1.5 h following oral administration of prodrug 5. Similarly, the average concentration of IMQ in MLNs and ILNs also improved following the oral administration of prodrug 8. Additionally, the BD studies showed that the non-specific distribution of IMQ into various organs and tissues was reduced following the oral administration of prodrugs in comparison to the oral administration of unmodified IMQ. This PhD project suggests that the highly lipophilic prodrug approach is a simple but powerful method that can efficiently deliver IMQ to intestinal lymphatics following oral administration. In addition, this study demonstrates the feasibility of using amide-based prodrugs for general amine-containing compounds for intestinal lymphatic targeting.